Play, Creativity, and Social Movements : If I Can't Dance, It's Not My Revolution. - Shepard, Benjamin, 1969- (Routledge advances in sociology., 2011)
The streets of cities around the world have been filled with a new theatrical model of protest, with creativity, fun, pleasure, and play as the cornerstones of this new approach. This book examines the historical use and development of 'play' as well as the recent ways in which it has infused protest and community building.